2015
DOI: 10.20506/standz.2790
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Dog Owners Regarding Rabies and Dog Bites in Bicol Region

Abstract: This study was conducted in selected provinces of Bicol Region from April 2015 to May 2015 to describe the knowledge, attitudes and practices (KAP) of dog owners regarding rabies and dog bites. A purposive sampling was used in selecting the respondents of the study. Frequencies were tabulated for all variables. Of the 1,200 respondents, 2,193 dogs were recorded making a 2:1 ratio of dogs to householders in this particular study. Among these dogs 58% were vaccinated against rabies. The majority of the ones taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Table 4 summarizes other studies in the Philippines in which the owned dog population and the total dog population were estimated in various areas of the country. In some studies, a purposive sampling methodology was adopted in which dog-or pet-owning households were surveyed [13,15], while in others, a sampling technique that combined random and systematic methods was undertaken [14,16]. This combined random and systematic method is also commonly described in other studies conducted in Africa [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 4 summarizes other studies in the Philippines in which the owned dog population and the total dog population were estimated in various areas of the country. In some studies, a purposive sampling methodology was adopted in which dog-or pet-owning households were surveyed [13,15], while in others, a sampling technique that combined random and systematic methods was undertaken [14,16]. This combined random and systematic method is also commonly described in other studies conducted in Africa [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This study, however, was quite limited, with only 64 dogowning households surveyed in Dumaguete [13]. In 2015, Bernales and Basitan conducted a study that included 1200 dog-owning households in the Bicol region and reported a dog: human ratio of 2:1 [15]. Although both studies provide insight into the dog population, they present an inflated estimate because a purposive sampling method was used to select the dogowning households in both.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations